2020
DOI: 10.1519/jsc.0000000000002542
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Y-Balance Performance in Elite Figure Skaters

Abstract: Asymmetrical dynamic balance compared to normative populations have been associated with increased risk of injury in athletes, however it is unclear if the current data are similar to balance performance in figure skaters. Therefore, the purpose of this study was to compare performance on the y-balance test between sexes and disciplines in elite figure skaters. Thirty-two senior level figure skaters from 3 different disciplines (singles, dance, pair) completed the y-balance test on the take-off and landing leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Several studies utilizing heterogeneous populations (D I athletes [10,13], D II women’s BB/women’s volleyball [12] and D III athletes [unpublished data, 2019] [24]) have reported no association between preseason scores and sports injury. Potential reasons for the finding of no association between test scores and injury may be due to differences in injury risk between sports or differences in normalized reach performance between genders [16,25,26,27]. Contrary to the findings associated with the aforementioned studies, two studies utilizing homogeneous populations (male collegiate football players = 59 [7] and male professional and amateur soccer players = 74 [8]) have reported significant relationships between either composite score [7] or reach asymmetry [8] and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies utilizing heterogeneous populations (D I athletes [10,13], D II women’s BB/women’s volleyball [12] and D III athletes [unpublished data, 2019] [24]) have reported no association between preseason scores and sports injury. Potential reasons for the finding of no association between test scores and injury may be due to differences in injury risk between sports or differences in normalized reach performance between genders [16,25,26,27]. Contrary to the findings associated with the aforementioned studies, two studies utilizing homogeneous populations (male collegiate football players = 59 [7] and male professional and amateur soccer players = 74 [8]) have reported significant relationships between either composite score [7] or reach asymmetry [8] and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Full text eligibility assessment of the remaining 411 articles resulted in 57 articles with 4 in multiple categories (Figure 1). 3,9,[12][13][14] Nine studies 9,25,33,40,46,[51][52][53][54] assessed reliability, 36 studies [12][13][14][23][24][25][26][27][28][29][30]32,35,37,38,[41][42][43][44][45]47,49,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] examined differences in the performance on the YBT-LQ in different populations or reported mean performance on the YBT-LQ in a specific population, and 16 studies 3,3...…”
Section: Study Selectionmentioning
confidence: 99%
“…When competition level was considered alone (middle school, high school, college, professional), no differences were observed for the anterior (p = 0.05), posteromedial (p = 0.69), posterolateral (p = 0.62), or composite score (p = 0.15) (Figure 3, 4, 5, 6). [12][13][14][23][24][25][26][27][28][29][30]32,35,37,38,[41][42][43][44][45]47,49,[54][55][56][57][58][59][60][61][62][63][64][65][66][67]…”
Section: Competition Level Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,7,13 It is important to note that several studies have reported normative data for the YBT-LQ in various athletic and military populations. [14][15][16][17][18][19][20][21][22][23] YBT-LQ scores may differ between athletes based on sport participation, gender, or competition level; therefore a clinician should compare their patient's scores with those from a homogeneous sample. 16,18,24 Only two studies have reported normative data for collegiate VB players with each study marked by limitations.…”
Section: Introductionmentioning
confidence: 99%